Website-Based laboratory management system of UNHAN RI Chemical Laboratory - Karomah, Sufi Naylil; Bimorogo, Sembada Denrineksa; Kurniadi, Tedi; Sigalingging, Miranda B.M; Diadra, M. Fadhil; Nasyira, M. Sulthan; Brata, Daffa Mahdy; Ma’ruf, Azzam Amar (Institute of Computer Science (IOCS), 2026)
Effective laboratory management plays a crucial role in supporting academic and research activities in higher education; however, many university laboratories still rely on manual recording systems that lead to data inconsistencies, weak inventory control, and limited monitoring of material and equipment usage. These challenges are particularly critical in chemistry laboratories with high-intensity utilization and strict governance requirements, such as those in defense-oriented institutions. This study aims to develop and implement a web-based Laboratory Management System, namely LABUNICA, to improve the efficiency, accuracy, and accountability of laboratory operations in the Chemical Laboratory of Universitas Pertahanan Republik Indonesia. The system was developed using the Rapid Application Development (RAD) method, emphasizing iterative prototyping, direct user involvement, and continuous refinement based on operational feedback. System analysis and design were conducted through interviews, observations, and UML-based modeling, followed by front-end and back-end development and black-box testing. The results indicate that LABUNICA successfully streamlines laboratory workflows, reduces redundancy in usage recording, enhances real-time inventory monitoring, and supports role-based access control for users and administrators. The implementation of LABUNICA improves documentation accuracy, system usability, and operational transparency compared to previous manual practices. This study contributes to the laboratory information system literature by demonstrating the effectiveness of a user-centered, web-based management system tailored to the operational characteristics of a defense university chemistry laboratory, with practical implications for digital laboratory governance in higher education institutions.